PEMBELAJARAN MENULIS TEKS BIOGRAFI PADA SISWA SMK KELAS X DENGAN MENGGUNAKAN MODEL EXAMPLE NON-EXAMPLE BERBANTUAN MEDIA AUDIOVISUAL YOUTUBE - Ghazani, Alma (IKIP Siliwangi, 2020)
Learning is a form of interaction between teachers and students in order to achieve an expected learning goal. This study aims to examine the scenario and implementation of learning to write biographical text for grade X students using the example non-example model assisted by YouTube audiovisual media, examine the responses of teachers and grade X students to learn how to write biographical texts using the media-assisted example non-example model YouTube audiovisual, and examine the difficulties experienced by students in grade X in completing assignments to write biographical texts. The method used is a qualitative descriptive method. The research subjects were students of SMK Sangkuriang 1 Cimahi class X OTKP 1 with a total of 36 students. by being treated during three meetings, the results in the field showed that the teacher activity sheet got a percentage of 89.58%, and from the student activity sheet that was obtained by 91.18%, so the teacher and student activity sheets were included in the very high category. Then the teacher and student responses to learning to write biographical texts by using a non-example example model assisted by audiovisual media YouTube is very good with the following percentage, the results of the teacher's questionnaire responses reached 55% so that they are included in the high category, while the results of the student response questionnaire reached 58.65% so it is included in the high category. Difficulties experienced by students based on cognitive values obtained by the average student students difficulty in determining linguistic rules in biographical texts, then there are still students who do not pay attention to the three applicable biographical text structures, and in the writing section there are still students who do not pay attention to punctuation, capital letters, and neatness in writing.